2017
DOI: 10.1016/j.jacep.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Atrial Conduction Delay Revealed by Multisite Incremental Atrial Pacing is an Independent Marker of Remodeling in Human Atrial Fibrillation

Abstract: ObjectivesThis study sought to characterize direction-dependent and coupling interval–dependent changes in left atrial conduction and electrogram morphology in uniformly classified patients with paroxysmal atrial fibrillation (AF) and normal bipolar voltage mapping.BackgroundAlthough AF classifications are based on arrhythmia duration, the clinical course, and treatment response vary between patients within these groups. Electrophysiological mechanisms responsible for this variability are incompletely describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…The mid CS was chosen to ensure that the LA activated uniformly. Previous studies have shown discrepancies between LA voltage under HRA and CS pacing conditions, 30 potentially due to fusion of LA activation via the septum and Bachman's bundle. Whether different voltage-rate effects would be revealed by alternative activation vectors is not answered by these data but is worthy of further study, particularly given the lack of relationship between LA voltage in sinus rhythm and AF (where multiple, chaotic activation vectors are likely to be present).…”
Section: Limitationsmentioning
confidence: 95%
“…The mid CS was chosen to ensure that the LA activated uniformly. Previous studies have shown discrepancies between LA voltage under HRA and CS pacing conditions, 30 potentially due to fusion of LA activation via the septum and Bachman's bundle. Whether different voltage-rate effects would be revealed by alternative activation vectors is not answered by these data but is worthy of further study, particularly given the lack of relationship between LA voltage in sinus rhythm and AF (where multiple, chaotic activation vectors are likely to be present).…”
Section: Limitationsmentioning
confidence: 95%
“…Direction-dependent effects were previously demonstrated for much larger ventricular signals [15] but have also recently been demonstrated by comparing sinus rhythm/high right atrial pacing to coronary sinus pacing in the atrium. In contrast to predictions from simulated data, these effects are highly variable indicating that voltage change could not be used, for example, to infer activation direction [16].…”
Section: Technical Aspects Of Voltage Mappingmentioning
confidence: 99%
“…Using high-density contact mapping, Sonoda et al found that LA activation time was longer in patients with persistent compared to paroxysmal AF, despite homogeneous activation patterns in both groups [2]. Interestingly, a recent study [32] suggested that, in patients undergoing paroxysmal AF ablation, decremental conduction properties in the LA predicted a higher risk of AF recurrence during a 2-year follow-up; the association was not statistically significant. In conclusion, these measures may help assess the vulnerability of atrial tissue to AF, but evidence is insufficient for clinical applications.…”
Section: Alternative Measures Of Intra-atrial Conduction Abnormalitiesmentioning
confidence: 99%